Freefall : Free markets, and the sinking of the global economy - Stiglitz, Joseph E. (Allen Lane, 2010)
Nobel Laureate Joseph E. Stiglitz explains how America exported bad economics, bad policies and bad behavior to the rest of the world. When World markets began to fail, America put together a haphazard response. Stiglitz outlines his responses to address the inequalities in the global financial and challenges economists for good ideas.